Echocardiographic Diagnosis of Incidentally Found Left Coronary Artery to Pulmonary Artery Fistula in an 11-Year-Old Girl - Chen, Bo-Hau; Lin, Chu-Chuan; Weng, Ken-Pen; Wu, Huang-Wei; Chien, Jen-Hung; Huang, Shih-Ming (Acta Cardiologica Sinica, 2016)
We report on a healthy 11-year-old girl who presented to our facility with sudden onset of fainting in a strenuous running course. Transthoracic echocardiography at short-axis view showed a diastolic flow into the main pulmonary artery (PA). The diagnosis of left anterior descending artery (LAD) to PA fistula was documented by cardiac computed tomography and catheterization. Interventional therapy of LAD to the main PA fistula was not performed because of no evidence of myocardial ischemia or significant hemodynamic change. Presently, the patient remains asymptomatic. Coronary fistula with an incidence of about 0.1-0.8% is very rare and may be undetected, particularly in pediatric patients without cardiac murmur.We herein describe the diagnostic approach and discuss the current treatment modalities